A first test of unattended, acoustic recorders for monitoring Capercaillie Tetrao urogallus lekking activity. Issue 2 (3rd April 2018) - Abrahams, Carlos; Denny, Matthew J. H.
ABSTRACT: Capsule: Automated acoustic recording can be used as a valuable survey technique for Capercaillie Tetrao urogallus leks, improving the quality and quantity of field data for this endangered bird species. However, more development work and testing against traditional methods are needed to establish optimal working practices. Aims: This study aims to determine whether Capercaillie vocalizations can be recognized in lek recordings, whether this can be automated using readily available software, and whether the number of calls resulting varies with location, weather conditions, date and time of day. Methods: Unattended recording devices and semi-automated call classification software were used to record and analyse the display calls of Capercaillie at three known lek sites in Scotland over a two-week period. Results: Capercaillie calls were successfully and rapidly identified within a data set that included the vocalizations of other bird species and environmental noise. Calls could be readily recognized to species level using a combination of unsupervised software and manual analysis. The number of calls varied by time and date, by recorder/microphone location at the lek site, and with weather conditions. This information can be used to better target future acoustic monitoring and improve the quality of existing traditional lek surveys. Conclusion: Bioacoustic methods provide a practical and cost-effective way to determine habitat occupancy and activity levels by a vocally distinctive bird species. Following further testing alongside traditional counting methods, it could offer a significant new approach towards more effective monitoring of local population levels for Capercaillie and other species of conservation concern.